EXPLORING MOTIVATION FOR THE CONTINUOUS USE OF CHATGPT AT THE LIBRARY SCIENCE LEARNING - Yanuar Putri Ayu El Dina; Moh Safii; Setiawan Setiawan; Sokhibul Ansor (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
ChatGPT, as a form of artificial intelligence, has become a popular tool among students. This study aims to explore the motivations of Library Science students at Universitas Negeri Malang in continuously using ChatGPT in the context of academic learning. Using the Self-Determination Theory-ChatGPT (SDT-ChatGPT) framework, this study analyzes the motivational factors underlying students' use of technology, focusing on extrinsic motivation, intrinsic motivation, autonomy, competence, connectedness, and challenge. This study uses qualitative methods, with data collected through interviews and documentation. The results of this study indicate that students' initial use of ChatGPT is generally influenced by external factors rather than personal desire. However, as their freedom in using ChatGPT increases, their motivation becomes more internal, characterized by increased comfort in learning and a sense of attachment to the tool. Students also face challenges in its use, such as the limitations of the free version, the quality of information, and the risk of dependence on the tool.